The effects of AI on startups and their business models - Taran, Alexey (2024)
Artificial intelligence (AI) introduced a lot of opportunities in many sectors, transforming how startups develop, deliver, and capture value. This thesis investigates the impact of AI on startups and their business models. Most important insights are received in how AI effects strategic decision making, operational activities, customer relations, and market positioning by conducting twenty semi-structured in-depth interviews with startups’ owners, co-founders, and CEO level employees from different sectors and regions. From the interviews it is clearly seen how artificial intelligence let startups automate their operational activities, improve customer satisfaction, and creates new opportunities for business model development. On the other hand, this thesis identifies barriers for AI implementation, such as ethical considerations, complexity of legislation, and costs of investment. The investigation finds diverse patterns of AI integration. For early-stage startups it helps them more with operational activities, while for those who operate for some time, it allows them to redefine their value propositions. This thesis suggests that, even though artificial intelligence has huge potential , its implementation requires strategic vision and a combination of technology and human supervision. Startups may gain a competitive advantage and adapt to quickly changing competitive landscape by overcoming these barriers.